2021
DOI: 10.1029/2020gl090509
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly Evolving Controls of Landslides After a Strong Earthquake and Implications for Hazard Assessments

Abstract: Rainfall-induced remobilizations of coseismic landslide deposits, propagating from hillslopes to downstream (Dahlquist & West, 2019), are a typical hazard in areas affected by earthquake-induced landslides (X. Fan et al., 2019a). These deposits are typically constituted by loose materials with significant amounts of fines, hence they are susceptible to sudden collapse and liquefaction upon loss of suction or pore water pressure increase (Hu et al., 2017, 2018). Debris remobilization events may occur in the ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 69 publications
2
50
1
Order By: Relevance
“…Following this idea, we minimized the chance of interactions among the covariates (see the multicollinearity test in Figure S1 , supplementary information) and chose, for instance, not to use those expressing the SU orientation. We did not consider the bedrock lithology as previous studies found that it had little influence on the coseismic 60 and postseismic 7 pictures in the epicentral region owing to its uniformity (mostly granite). Similarly, available precipitation metrics were not found to exert a prime control on the postseismic evolution of landslide activity 7 , owing to the smooth spatial changes of cumulative values observed in the study area.…”
Section: Resultsmentioning
confidence: 99%
“…Following this idea, we minimized the chance of interactions among the covariates (see the multicollinearity test in Figure S1 , supplementary information) and chose, for instance, not to use those expressing the SU orientation. We did not consider the bedrock lithology as previous studies found that it had little influence on the coseismic 60 and postseismic 7 pictures in the epicentral region owing to its uniformity (mostly granite). Similarly, available precipitation metrics were not found to exert a prime control on the postseismic evolution of landslide activity 7 , owing to the smooth spatial changes of cumulative values observed in the study area.…”
Section: Resultsmentioning
confidence: 99%
“…For input features derived from topography, we used the 30 m Shuttle Radar Topography Mission (SRTM) digital elevation model (DEM) (Farr et al, 2007). When processing the SAR data, this DEM was resampled to a resolution of 20 m × 22 m using linear interpolation.…”
Section: Topographic Featuresmentioning
confidence: 99%
“…Few examples of long-runout debris flows triggered by earthquakes have been described on active volcanoes (Schuster et al, 1996;Scott et al, 2001). In Mexico, a M w 6.5 earthquake that occurred in 1920 induced several landslides in the Pico de Orizaba-Cofre de Perote volcanic chain that transformed into debris flows with catastrophic effects for villages along the Huizilapan ravine (Camacho, 1920;Flores, 1922). More recently, several thousands of shallow landslides were triggered by the TecomĂĄn earthquake of 21 January 2003 (M w 7.6) in the volcanic highlands north and northwest of Colima City (Keefer et al, 2006).…”
Section: Introductionmentioning
confidence: 99%